Fatigue and cyclic plasticity of 304L stainless steel under axial-torsional loading at room temperature. (August 2019) - Bemfica, C.; Carneiro, L.; Mamiya, E.N.; Castro, F.C.
Highlights: Martensitic phase transformation was not observed for all loading paths. Neither accumulated plastic strain nor amplitude could predict phase transformation. Cyclic Young's and shear moduli did not vary due to martensitic transformation. Fatigue life estimates were not significantly influenced by secondary hardening. Crack orientation depended on the strain amplitude for all paths but the axial one. Abstract: This work investigates the axial-torsional fatigue and cyclic deformation behaviour of 304L stainless steel at room temperature. The testing programme included four fully reversed strain-controlled loading paths (axial, torsional, proportional axial-torsional, and 90° out-of-phase axial-torsional) and a fully reversed shear strain-controlled with static axial stress. The experiments were carried out at equivalent strain amplitudes ranging from 0.20% to 1.00%, resulting in fatigue lives from 10 2 to 10 6 cycles. For axial, torsional, and torsional with axial static stress loading, secondary hardening related to martensitic transformation was observed, while it did not occur for nonproportional loading. For proportional loading, secondary hardening occurred only for an equivalent strain amplitude equal to or greater than 0.80%. Neither the accumulated plastic strain nor the equivalent plastic strain amplitude could predict whether secondary hardening would occur for the investigated loading conditions. Almost no variation in the cyclic Young's and shear moduli with the number of loading cycles was observed even for the tests that exhibited considerable secondary hardening. Fatigue life estimates calculated using the stress-strain hysteresis loops at maximum softening and at half-life were similar for the Smith–Watson–Topper, Fatemi–Socie, and Jiang models. It was observed that macroscopic surface crack orientation depends on the equivalent strain amplitude for torsional, proportional, nonproportional and torsional with static stress loading. The capability of the models to estimate the observed crack orientations is discussed.